Competition policy reform in Europe and Germany - Institutional change in the light of digitization - Oliver Budzinski; Annika Stöhr (Technische Universität Ilmenau, Institut für Volkswirtschaftslehre, 2018)
The ubiquitous process of digitization changes economic competition on markets in several ways and leads to the emergence of new business models. The increasing roles of digital platforms as well as data-driven markets represent two relevant examples. These developments challenge competition policy, which must consider the special economic characteristics of digital goods and markets. In Germany, national competition law was amended in 2017 in order to accommodate for digitization-driven changes in the economy and plans for further changes are already discussed. We review this institutional change from an economics perspective and argue that most of the reform's elements point into the right direction. However, some upcoming challenges may have been overlooked so far. Furthermore, we discuss whether European competition policy should follow the paragon of the German reform and amend its institutional framework accordingly. We find scope for reform particularly regarding data-driven markets, whereas platform economics appear to be already well-established.
Keywords: L40; K21; L86; L82; L81; L10; L15; D80; 330; competition policy; antitrust; industrial economics; digitization; media economics; institutional economics; industrial organization; big data; algorithms; platform economics; two-sided markets; personalized data; privacy; internet economics; consumer protection